Mycobacterium tuberculosisInduction of Heme Oxygenase-1 Expression Is Dependent on Oxidative Stress and Reflects Treatment Outcomes - Rockwood, Neesha (2017)
Intramural Research Program of the NIAID and by a grant from the National Institutes of Health (NIH) U01AI115940. RW is supported by the Francis Crick Institute which receives its core funding from Câncer Research UK (FC00110218), the UK Medical Research Council